Microprocessor based DC chopper drive for electric traction - Akay, Metin. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
In this thesis a microprocessor based DC chopper drive for electric vehicles is designed and implemented. The DC motor is fed by a two-quadrant chopper, the firing pulse of which is set directly by the microcomputer. The system is centered around a MC6802 microprocessor. Attention here is focused upon the motoring and regenerative braking of a DC motor. The PID (Proportional-Integral-Derivative) algorithm implemented in the microcomputer, acts on the error to result in the digital control pulses to drive the choppers. In the last two chapters, in addition to these, the experimental results are analyzed and system performance is evaluated. Further suggestions for improvement are given.
Keywords: Microprocessors.; Electric equipment.